Head and Neck Cancer in Pan-American Notable People: An International Survey - Josefina Martínez-Ramírez; Cristina Saldivia-Siracusa; Maria Eduarda Pérez-de-Oliveira; Ana Gabriela Costa Normando; Luiz Paulo Kowalski; Maria Paula Curado; Lady Paola Aristizabal Arboleda; Ana Carolina Prado-Ribeiro; Leonor-Victoria González-Pérez; Gisele Aparecida Fernandes; Florence Juana Maria Cuadra-Zelaya; Pablo Agustin Vargas; et al. (Dentistry Journal)
Background: The study of notable people as advocates for raising cancer awareness began in the latter decades of the 20th century. This research aimed to identify Pan-American notable people with head and neck cancer (HNC) and to explore senior health professionals’ perspectives on communicating stories of notable patients with HNC to promote prevention. Method: A cross-sectional survey was conducted using an online questionnaire designed in REDCap and administered to 32 senior health professionals with long-standing academic and clinical backgrounds in HNC. In addition, a structured literature review was performed on PubMed, Scopus, EMBASE, Web of Science, LILACS, and gray literature. Results: 18 notable figures were successfully identified from the survey, and 24 from the literature review. These individuals came from the United States, Brazil, Argentina, Mexico, El Salvador, Chile, Colombia, and Peru, and were recognized primarily for their performances as actors, artists, musicians, and athletes. The professionals’ outlooks were positive, with 31 (96.9%) agreeing that disseminating these stories can contribute to reducing risk behaviors. Furthermore, all participants (100%) agreed that such stories can promote early detection of HNC, primarily through social media, followed by the internet, and television. Conclusions: The study identified notable individuals and gathered positive perspectives from professionals. Our results suggest that notable people could serve as potential advocates for HNC prevention. Further research is warranted to explore the potential of this prevention strategy.